Assessing food value chain pathways, linkages and impacts for better nutrition of vulnerable groups. (April 2017) - Maestre, Mar; Poole, Nigel; Henson, Spencer
Highlights: We link post-farm gate value chain (PFGVC), agriculture and nutrition. Provide a tool to assess the effectiveness of PFGVC at delivering nutritious food. Examine the pathways to deliver nutritious food to vulnerable population. Key outcomes and requirements for PFGVC to be successful at delivering nutritious food. Abstract: This article offers insights into assessing the effectiveness of post farm-gate agri-food value chains at improving the nutrition intake of vulnerable groups. It develops a conceptual framework integrating the value chain concepts with agriculture and nutrition, and identifies key outcomes and requirements for value chains to be successful at delivering substantive and sustained consumption of nutrient-dense foods by poor households. Other frameworks linking value chains with nutrition have been published, but this article provides the analytical lens to assess post-farm-gate value chains. To achieve improvements in the intake of nutritious foods by the target populations food must be: safe to eat on a sustained basis; nutrient dense at the point of consumption; and consumed in adequate amounts on a sustained basis. This shifts the focus to the role of public actions and policy in terms of shaping the functioning of food value chains. By assessing the limits of what business can and cannot contribute in a given market context, policy-makers and other relevant stakeholders will be more capable of creating an appropriate institutional environment that shapes how value chains operate for the benefit of vulnerable target groups, designing and implementing effective policies and strategies with respect to the role and use of market-based interventions.